2018
DOI: 10.1111/1541-4337.12400
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Oligosaccharides and Glycoconjugates Content in Human Milk and the Development of the Gut Barrier

Abstract: The intestinal immune barrier is considered to be the gatekeeper of the human body and rapidly develops directly after birth. Many pre‐ and postnatal factors influence the development of the gut‐barrier, which is composed of the microbiota, the mucus, the epithelial layer and the mucosal immune system. Even minor disturbances during barrier development can have consequences for health far into adulthood. Here we critically discuss the current knowledge on which pre‐ and postnatal factors influence development,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 262 publications
(291 reference statements)
0
15
0
1
Order By: Relevance
“…Their concentrations in maternal milk vary according to factors such as day of lactation, mother's genetic secretor status, and birth type, but large interlaboratory variations have also been reported as reviewed previously [52]. HMOs of different structures differentially affect the function of the gut barrier of the infant helping to maintain gut health [53]. A recent clinical trial in adults showed that supplementing the diet with HMOs could be a valuable strategy to shape the human gut microbiota and specifically promote the growth of beneficial bifidobacteria [18].…”
Section: Discussionmentioning
confidence: 98%
“…Their concentrations in maternal milk vary according to factors such as day of lactation, mother's genetic secretor status, and birth type, but large interlaboratory variations have also been reported as reviewed previously [52]. HMOs of different structures differentially affect the function of the gut barrier of the infant helping to maintain gut health [53]. A recent clinical trial in adults showed that supplementing the diet with HMOs could be a valuable strategy to shape the human gut microbiota and specifically promote the growth of beneficial bifidobacteria [18].…”
Section: Discussionmentioning
confidence: 98%
“…[13] The latter, gut barrier function, is provided by tightly connected epithelial cells and mucus. hMOs are known to enhance epithelial barrier, [20,21] but the relative effects of individual oligosaccharides on stimulate mucus function have not been studied yet. HMOs are also subject to modifications during passage through the gastrointestinal tract.…”
Section: Introductionmentioning
confidence: 99%
“…The intestinal mucosa of a healthy adult contains more than 80% of the body's immune cells, which makes the gastrointestinal tract the largest immunologically active organ of the human body (Lewis and Blutt 2019). Its primary function is to protect the human body from undesired intruders from the lumen of the intestine while at the same time inducing tolerance to the 100 trillion bacteria that are needed for digestive processes and for production of beneficial fermentation products such as short chain fatty acids (SCFAs) (Figueroa-Lozano and de Vos 2019;McLeod et al 2019). The mucosal immune system is integrated into a physical barrier which is composed of a mucus layer and closely connected epithelial cells that protect the host from the harsh luminal content of the gut (Okumura and Takeda 2017).…”
Section: The Intestinal Immune Systemmentioning
confidence: 99%
“…It is assumed that also closing the barrier is supported by bioactive components in mother milk (Cacho and Lawrence 2017). In addition, the bioactive molecules in mother milk support colonization of the more than 100 trillion microbiota in the small and large intestine that digest foods and produce fermentation products that are needed to support our metabolism, immunity and brain health (Figueroa-Lozano and de Vos 2019;McLeod et al 2019).…”
Section: Introductionmentioning
confidence: 99%